In vitro degradation and in vivo osteogenesis of Mg-Zn-Nd-Zr/HA composites prepared by friction stir processing - Wen Zhang; Jiarui Lu; Lili Tan; Dingrui Ni; Ran Zhang; Qing Zhou; Ke Yang; Qiang Wang (Journal of Magnesium and Alloys)
Biodegradable magnesium-matrix composites (BMMCs) added with bone-like compounds such as hydroxyapatite (HA) have promising orthopedic application potential, but the in vivo results of BMMCs are insufficient, and the difference between in vitro and in vivo are not clarified. In this work, Mg-Zn-Nd-Zr/(10/15/20wt%) HA (Ca10(PO4)6OH2) composites were prepared through friction stirring processing (FSP). It was found that corrosion rate of the composites increased with increase of the HA content, where the corrosion rate from hydrogen evolution of the Mg/10wt% HA was about 0.107 mm/y, showing better corrosion resistance compared with other BMMCs, and the agglomeration of HA powders significantly aggravated the localized corrosion. The ALP specific activity of the MC3T3-E1 cells cultured for 14 days with Mg/10wt% HA (2.12 IU/mg) was higher than that of the matrix (1.85 IU/mg), but there was no difference with the FSP group (2.13 IU/mg). In the early implantation of the rabbit femur, bone volume fraction (BV/TV) of Mg/10wt% HA was 10.69, which was higher than that of the FSP group (6.35). The histological staining showed that the Mg/10wt% HA implant was surrounded by more trabecular bone tissue, exhibiting better osteoinductive regeneration. The Mg-Zn-Nd-Zr/HA composites exhibit higher osteogenic activity in vivo differently from in vitro osteogenic expression.